Severe Neurological Sequelae after a Recreational Dose of LSD. Issue 7 (8th October 2020) - Aakerøy, Rachel; Brede, Wenche Rødseth; Stølen, Stian Bergseng; Krabseth, Hege-Merete; Michelsen, Lisbeth Solem; Andreassen, Trine Naalsund; Ader, Tiina; Frost, Joachim; Slettom, Grete; Steihaug, Ole Martin; Slørdal, Lars
Abstract: A young man with an unremarkable medical history suffered a seizure with subsequent cardiorespiratory arrest and severe neurological sequelae after ingesting a blotter. Analysis of a similar blotter and a serum sample obtained 3 h after the event detected lysergic acid diethylamide (LSD) at an amount of 300 µg in the blotter and at a concentration of 4.0 ng/mL (12.4 nmol/L) in the serum. No other drugs were present in concentrations which may confer significant effects. In addition, no individual traits which would make the patient particularly susceptible to adverse LSD effects have subsequently been identified. This suggests that LSD may confer toxic effects in previously healthy individuals.